1985
DOI: 10.1177/001872678503800602
|View full text |Cite
|
Sign up to set email alerts
|

Factors Differentiating Grievants and Nongrievants

Abstract: Previous attempts at identifying factors differentiating individuals who file grievances from those who do not have focused on demographic and job-related variables. These efforts have yielded inconsistent results and have not explained much of the variance in grievance-filing behavior. This line of research is extended in this study by presenting a model of individual grievance-filing behavior that includes a number of variables measuring attitudes toward work and unions. Such factors have been found associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 12 publications
1
29
0
Order By: Relevance
“…Prior research supports this assertion: Low job satisfaction has been shown to be associated with destructive behaviors such as intentions to quit (Rosse & Hulin, 1985), actual quitting (Abelson, 1987;Colarelli, Dean, & Konstans, 1987;O'Connor, Pooyan, Weekly, Peters, Frank, & Erenkrantz, 1984), absences (Blau, 1985;Rosse & Hulin, 1985), and lateness (Blau, 1985). In contrast, high job satisfaction has been linked with voice-like behaviors such as suggesting improvements and grievance filing (Allen & Keaveny, 1985;Dalton & Todor, 1982;Price, Dewire, Nowack, Schenkel, & Ronan, 1976;VanZelst & Kerr, 1953) as well as with loyalist behaviors such as good citizenship behavior and job commitment (Aranya, Kuchnir, & Valency, 1986;Bateman & Organ, 1983;Smith, Organ, & Near, 1983;Ferris & Aranya, 1983).…”
Section: Predicting the Responsesmentioning
confidence: 97%
“…Prior research supports this assertion: Low job satisfaction has been shown to be associated with destructive behaviors such as intentions to quit (Rosse & Hulin, 1985), actual quitting (Abelson, 1987;Colarelli, Dean, & Konstans, 1987;O'Connor, Pooyan, Weekly, Peters, Frank, & Erenkrantz, 1984), absences (Blau, 1985;Rosse & Hulin, 1985), and lateness (Blau, 1985). In contrast, high job satisfaction has been linked with voice-like behaviors such as suggesting improvements and grievance filing (Allen & Keaveny, 1985;Dalton & Todor, 1982;Price, Dewire, Nowack, Schenkel, & Ronan, 1976;VanZelst & Kerr, 1953) as well as with loyalist behaviors such as good citizenship behavior and job commitment (Aranya, Kuchnir, & Valency, 1986;Bateman & Organ, 1983;Smith, Organ, & Near, 1983;Ferris & Aranya, 1983).…”
Section: Predicting the Responsesmentioning
confidence: 97%
“…Perceived workplace discrimination may also result in grievances and legal action (Allen and Keaveny 1985).…”
mentioning
confidence: 99%
“…Also, Kochan (1979) did not find that such variables influenced the propensity to unionize. Allen and Keaveny (1985) did find that grievants tended to be slightly younger than nongrievants, but found no differences for other demographic factors such as hourly wages or seniority. Even so, for the present study, the archival sources of these data did not allow control for these factors.…”
Section: Discussionmentioning
confidence: 82%